2018
DOI: 10.1097/ta.0000000000001743
|View full text |Cite
|
Sign up to set email alerts
|

Variability in management of blunt liver trauma and contribution of level of American College of Surgeons Committee on Trauma verification status on mortality

Abstract: Care management, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 21 publications
0
25
1
1
Order By: Relevance
“…Active contrast extravasation is a sign of active hemorrhage [23]. CT scan may help in subsequent Table 3 AAST liver trauma classification [24][25][26][27][28][29][30][31][32]. Diagnostic peritoneal lavage (DPL) should be considered diagnostic modality in low-resource settings, where CT scan or US is not promptly available [33].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Active contrast extravasation is a sign of active hemorrhage [23]. CT scan may help in subsequent Table 3 AAST liver trauma classification [24][25][26][27][28][29][30][31][32]. Diagnostic peritoneal lavage (DPL) should be considered diagnostic modality in low-resource settings, where CT scan or US is not promptly available [33].…”
Section: Diagnosismentioning
confidence: 99%
“…In any case, these patients should undergo serial blood test: increasing levels of transaminases could indicate the presence of intrahepatic parenchymal ischemia or rare cases of torsion of suprahepatic veins [64]. ICU admission may be indicated for moderate (WSES II) (AAST III) and severe (WSES III-IV) (AAST IV-V) liver trauma in order to reduce the mortality risk [26].…”
Section: Diagnosismentioning
confidence: 99%
“…Those major complications have previously been verified to have the highest attributable mortality among trauma patients. 13,14 To evaluate all-cause in-hospital mortality, early mortality, ICU admission, major complications, and treatment strategy, we used multilevel mixed-effects logistic regression models. To evaluate time to treatment, we used mixed-effects negative binomial regression models.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with high-grade solid organ injuries have improved outcomes when treated at tertiary trauma centers. 14,19 Unfortunately we were unable to evaluate transfer practices between majority, mixed-race, and minority hospitals. Hospital segregation may, in turn, affect health outcomes and service utilization differently than does residential segregation, for example, through racial differences in providers' medical practice patterns and in patients' access to high-quality providers and specialized services.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic instability is characterized by the following: heart rate > 120 bpm, systolic blood pressure < 90 mmHg, low urine output, increased respiratory rate (>30 respirations/minute), signs of skin vasoconstriction and altered level of consciousness [22]. Non-operative management necessitates medical centers capable of an accurate injury severity diagnosis, intensive management of patients, and prompt access to diagnostic modalities, interventional radiology, operation theater, and blood-blood products [20,23]. Ultrasound plays a significant role in the proper investigation of abdominal injuries.…”
Section: Initial Assessment and Investigationmentioning
confidence: 99%